"The contributions of Kurdish women to economic and social development in Jordan" - Dardouk, Ziad Abdel Jalil Ibrahim (Sulaimani Journal for Humanities, 2026)
This research aimed to demonstrate the contributions of Kurdish women to economic and social development in Jordan. The descriptive-analytical method was used to process and classify the data. A questionnaire was designed as the data collection instrument, used to gather information from the research sample. The data was then analyzed using the Statistical Package for the Social Sciences (SPSS). The research population consisted of Kurdish Jordanian women, numbering 540 according to official records. The research sample comprised 350 Kurdish Jordanian women. A total of 420 questionnaires were distributed, of which 339 were returned and deemed valid for statistical analysis. The research yielded several key findings, most notably that the greatest influence on Kurdish women's contribution to the economy is their perceived economic contribution. Specifically, every one-unit increase in a woman's perceived economic contribution leads to a 0.20-unit increase in her actual economic contribution. The research recommended increasing educational and training opportunities for Kurdish women, as this would enhance their skills, capabilities, and economic contribution. It also recommended raising awareness of the importance of Kurdish women's role in society, as this would lead to greater societal appreciation for their economic contributions.